Brand Image, Customer Satisfaction, And Brand Trust On Honda Motorcycle Customer Loyalty - Sari, Rias Fatika; Saputro, Edy Purwo (Jurnal Ilmu Manajemen Advantage, 2023)
Research is being conducted with the participation of students from the Faculty of Economics and Business at Muhammadiyah University Surakarta. The purpose of this research is to explore the link between the consumer loyalty behavior of Honda motorcycle customers and factors such as the perception of the brand, the level of customer satisfaction, and the level of trust in the brand. A study that was conducted not too long ago focused on students from the Faculty of Economics and Business at the University of Muhammadiyah Surakarta who owned two or more Honda motorbikes. It is possible to claim that the methodology used in this investigation is the quantitative approach. The research sample and demographic sample for this study are comprised of undergraduate students from the Faculty of Economics and Business at Muhammadiyah University of Surakarta who are in possession of several Honda motorcycles. The poll comprised a total of one hundred participants as a result of a well-planned screening procedure. The results of the research are based on the truthful evaluations that the respondents gave of the items that were included in the questionnaire. An application of multiple linear regression analysis was carried out on the data that was obtained by using SPSS version 23. The outcomes of the research indicate that the reputation of Honda motorbikes has a significant and detrimental effect on the company's ability to retain customers. On the other hand, positive and substantial effects are associated with customer satisfaction, and positive but moderate effects are associated with confidence in the brand.